Carbohydrate antigens in nipple aspirate fluid predict the presence of atypia and cancer in women requiring diagnostic breast biopsy - Vogeltanz-Holm Nancy; Holm Jeffrey E; Newton Jessica; Gui Gerald; Dickerson Marie; Deutscher Susan L; Kliethermes Beth; Hewett John E; Kumar Senthil R; Quinn Thomas P; Sauter Edward R (BMC Cancer, 2010)
Abstract Background The goal of this prospective study was to determine (a) concentrations of the carbohydrate biomarkers Thomsen Friedenreich (TF) antigen and its precursor, Tn antigen, in nipple discharge (ND) collected from women requiring biopsy because of a suspicious breast lesion; and (b) if concentration levels predicted pathologic diagnosis. Methods Adult women requiring biopsy to exclude breast cancer were enrolled and ND obtained. The samples from 124 women were analyzed using an anti-TF and anti-Tn monoclonal antibodies in direct immunoassay. Results The highest median concentration in ND for TF and Tn was in women with ductal carcinoma in situ (DCIS). TF was higher in women with 1) cancer (DCIS or invasive) vs. either no cancer (atypia or benign pathology, p = .048), or benign pathology (p = .018); and 2) abnormal (atypia or cancer) versus benign pathology (p = .016); and was more predictive of atypia or cancer in post- compared to premenopausal women. Tn was not predictive of disease. High TF concentration and age were independent predictors of disease, correctly classifying either cancer or abnormal vs. benign pathology 83% of the time in postmenopausal women. Conclusions TF concentrations in ND were higher in women with precancer and cancer compared to women with benign disease, and TF was an independent predictor of breast atypia and cancer. TF may prove useful in early breast cancer detection.